Creativity and entrepreneurship: The role of gender and personality - Efstathios Dimitriadis; Thomas Anastasiades; Despoina Karagiannidou; Maria Lagaki (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2018)
Purpose: This study examines the relationship between personality traits and creative behaviour, in an entrepreneurial environment. Moreover, an attempt was made to define the effect of gender on creative behaviour. Design/methodology/approach: Even though there are more women than men in Europe, female entrepreneurs represent only a third of the EU's self-employed. Additional factors, such as reconciling business and family, make entrepreneurship a less attractive option for them than for men. In order to achieve the objectives of this study research was conducted with the use of a structured questionnaire, during the months of February and March of 2017. The final sample size consists of 180 small and medium enterprises, from the region of North Greece. The instrument for content and construct validity was examined. Then, the hypotheses were examined using ANOVA, Correlation and Regression analysis. Findings: The results showed that 'Agreeableness', 'Openness to Experience', 'Conscientiousness', and 'Extraversion' are positively related with 'creative behaviour' of entrepreneurs. However, there is no strong evidence to predict the level of creativity by the personality traits. On the other hand, 'Neuroticism' is negatively correlated with creativity, but this relation is not significant. The results also indicate a statistically significant but not strong relation among the traits 'Agreeableness', 'Openness to Experience' and the performance of the enterprise. Research limitations/implications: There are some limitations in the study that can be addressed in the future; primarily, the study used subjective measures of firm performance instead of objective measures. Moreover, the sample size was small. A number of policy implications arise from this study. There needs to be a stronger recognition that the stereotypical role of women as sole careers is preventing future growth in female entrepreneurship. If the objective of future policy is to increase the number of women entrepreneurs, particularly in the current climate of global financial crisis and economic recession, it is imperative that we take account of the motivations of women who become entrepreneurs. Once the potential role of personality traits has been more clearly established, this can be used to inform policy making and decision making. Originality/value: To the best of our best knowledge, this is the first attempt at estimating the effects of gender and personality on creativity and entrepreneurship in Greece.
Keywords: M13; P17; 330; Entrepreneurship; Personality; Gender; Big Five Model